Relationship of Lipoprotein(a) to Variables of Coagulation in Hypertensive Subjects. (1st January 2001) - Sechi, Leonardo A.; De Marchi, Sergio
Abstract: Background: Coagulation factors are independent predictors of cardiovascular damage in the general population. The purpose of this study was to investigate the relationships between general cardiovascular risk factors, lipoprotein(a) (Lp(a)), and some hemostatic variables, and to characterize the isoforms of apolipoprotein(a) (apo(a)) in hypertensive subjects. Methods: Plasma lipids, apolipoproteins, Lp(a), apo(a) isoforms, fibrinogen, and parameters that directly reflect the coagulation activation were measured in 389 untreated essential hypertensive patients recruited at a hypertension clinic. Hypertensive patients were compared with 323 normotensive controls. Results: In normotensive subjects, Lp(a) concentrations were significantly correlated with fibrinogen ( r =0.138; P <0.02) but not D-dimer ( r =0.074; not significant). In hypertensive subjects, log Lp(a) concentrations were significantly correlated with age ( r =0.127; P <0.02), apo-B ( r =0.128; P <0.02), plasma fibrinogen ( r =0.193; P <0.001), and fibrin D-dimer ( r =0.200; P <0.001) levels, but not with body mass index, blood pressure, cholesterol, triglycerides, apo-AI, prothrombin fragment 1+2, and antithrombin III. The relationship of Lp(a) with fibrinogen (male: r =0.198, P <0.002; female: r =0.177, P <0.01) and D-dimer (male: r =0.211, P <0.002; female: r =0.188, P <0.01) was significant in both sexes, whereas the relationship of Lp(a) with age and apo-B was found only in males. Multivariate analysis showed that both fibrinogen and D-dimer were independently related with Lp(a). Elevated fibrinogen, D-dimer, and Lp(a) levels were significantly and independently associated with clinical evidence of atherosclerotic disease. Apo(a) phenotypes were analyzed to investigate the genetic background of the relationships between Lp(a) and coagulation parameters. In both hypertensive and normotensive subjects, Lp(a) levels were inversely correlated with apo(a) isoform protein size, whereas fibrinogen and D-dimer concentrations were comparable in patients with apo(a) isoforms of different size. Conclusions: The relationship between Lp(a) and clotting variables is significantly stronger in hypertensive than in normotensive subjects, providing a compelling argument for accelerated progression of atherothrombosis in these patients.